Research on Spatial-Temporal Variations of Cultivated Land in China Based on GlobeLand30 - Cheng, Hui; Wang, Xiaowei; Chen, Danling (Frontiers in Environmental Science, 2022)
The period from 2010 to 2020 is a period of rapid economic development in China, with the increasing population and the urbanization level reaching 63.89%. Cultivated land plays an extremely important role in China's food security. In order to grasp the spatial and temporal distribution and change of cultivated land use in China in time, based on GlobeLand30 data in 2010 and 2020, this study studied the spatial and temporal change characteristics of total cultivated land resources, cultivated land development and utilization degree, dynamic change degree of cultivated land utilization rate, and cultivated land use center and direction by using GIS technology, reclamation index, cultivated land utilization rate dynamic change degree model, cultivated land center shift model and standard deviation ellipse model. The results show that: ①The cultivated land area in China has changed greatly during 2010 to 2020, with the largest increase in cultivated land area in Inner Mongolia and Xinjiang, while the largest decrease in cultivated land area in Shandong, Jiangsu, Hebei, Guangdong, Henan and Zhejiang; ②The areas with the highest degree of cultivated land development and utilization are mainly concentrated in Shandong, Jiangsu, Henan, Anhui and other provinces in the east, while Qinghai, Tibet and Xinjiang have the lowest degree of cultivated land development and utilization; ③The regions with the highest dynamic change degree index of cultivated land utilization rate are mainly concentrated in Inner Mongolia, Xinjiang, Tibet and Qinghai, while the dynamic change degree index of cultivated land utilization rate in Liaoning, Hebei, Shandong, Jiangsu, Shanghai, Zhejiang and Guangdong shows obvious negative changes; ④The spatial and temporal migration of the center of gravity of cultivated land use in China shows the trend of "moving westward to northward", and the spatial distribution direction of cultivated land use roughly presents the overall characteristics of northeast-southwest direction. This study can effectively reveal the temporal and spatial variation characteristics of cultivated land use at provincial level in China based on GlobeLand30, and provide a scientific reference for further rational development, utilization and protection of cultivated land resources in China.